2013
DOI: 10.1007/s00774-013-0529-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating spine micro-architectural texture (via TBS) discriminates major osteoporotic fractures from controls both as well as and independent of site matched BMD: the Eastern European TBS study

Abstract: The aim of the study was to assess the clinical performance of the model combining areal bone mineral density (aBMD) at spine and microarchitecural texture (TBS) for the detection of the osteoporotic fracture. The Eastern European Study is a multicenter study (Serbia, Bulgaria, Romania and Ukraine) evaluating the role of TBS in routine clinical practice as a complement to aBMD. All scans were acquired on Hologic Discovery and GE Prodigy densitometers in a routine clinical manner. The additional clinical values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…Similar results were obtained in another age matched case-control study focusing on osteopenic subjects with vertebral fractures [9]. Vasic et al reported outcomes of the Eastern Europe study (EES), a multi-center study in different European countries that sought to evaluate the role of TBS in routine clinical practice as a complement to BMD and clinical risk factors [26].…”
Section: Discussionsupporting
confidence: 60%
“…Similar results were obtained in another age matched case-control study focusing on osteopenic subjects with vertebral fractures [9]. Vasic et al reported outcomes of the Eastern Europe study (EES), a multi-center study in different European countries that sought to evaluate the role of TBS in routine clinical practice as a complement to BMD and clinical risk factors [26].…”
Section: Discussionsupporting
confidence: 60%
“…In postmenopausal women, LS TBS was associated with fracture risk even after adjusting for central DXA BMD and/or FRAX clinical risk factors, such as age, weight, BMI, previous fracture, glucocorticoid use, presence of rheumatoid arthritis (RA), secondary osteoporosis, and high alcohol intake. Several studies have shown that, in postmenopausal women, the combination of LS TBS and BMD slightly improves fracture discrimination compared to BMD alone (25,26,29,35 In unadjusted models, the area under the receiver operating characteristic curve (AUC) was significantly greater for the combination LS BMD þ TBS than for LS BMD alone ( p 5 0.005), but the differences in the adjusted AUCs were not reported.…”
Section: Postmenopausal Womenmentioning
confidence: 82%
“…BMD at the LS, hip, and the lowest BMD T-score were also associated with fractures, with adjusted ORs ranged from 1.36 to 1.63. The Eastern European TBS study, multicenter, casecontrol trial, evaluated the association of TBS with major osteoporotic fractures in 1031 Caucasian women, aged 45e85 yr, with a BMI between 15 and 35 kg/m 2 (29). Subjects were recruited using the medical record database at 6 centers in East Europe.…”
Section: Postmenopausal Womenmentioning
confidence: 99%
“…Previous analyses have shown that lumbar spine TBS is a predictor of fracture risk, independent of BMD, but its inclusion in a multivariate risk model leads to only a small improvement in performance as measured by the AUROC. (7,8,(27)(28)(29)(30)(31) Prior studies have also examined the impact of TBS on risk assessment using NRI; (9,28,30,32) however, the large NRI obtained in some of these studies raises concerns over model miscalibration because other performance metrics were non-significant. (33) The results of the current study are in line with those of Schousboe and colleagues, (34) who reported NRI in fracture cases of þ0.033 (p < 0.005) for TBS-adjusted fracture risk prediction in older men (MrOS), with only a very small net decrease for NRI in men without fracture.…”
Section: Discussionmentioning
confidence: 99%